(untitled) (Damascus University Journal of agriculture sciences, 2021)
This study aimed to investigate the occurrence of entomopathogenic nematodes (EPN) in gardens and orchards of Damascus province, and to study the effect of environmental factors on the prevalence of EPN. This research was conducted during the period of 2011-2013. 250 soil samples were collected from the gardens and orchards in Damascus province, The presence of EPN was detected using the wax moth bait method, and white trap for collect infective juveniles. The presence rate of EPN in gardens and orchards of Damascus was 8.4%, the results showed presence of genera Steinernema and Heterorhabditis, the highest prevalence of EPN was in citrus 11.11%, followed by herbs 9.37%, and lawns 9.18%. The result showed a significant correlation between the presence of nematodes and soil texture ,the largest percentage of nematodes were found in the sandy Lummi soil and sandy clay Lummi texture. Also the presence of nematodes was influenced by method of irrigation. The results also showed that the prevalence of genera Steinernema was at moderate to low temperature, on the other hand Heterorhabditis was found at moderate temperatures and high temperatures.